2009
DOI: 10.1063/1.3259650
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on the enhancement of lithium storage capacity in boron doped graphene

Abstract: G. (2009). First-principles study on the enhancement of lithium storage capacity in boron doped graphene. Applied Physics Letters, 95 (18), 1-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 24 publications
6
59
0
Order By: Relevance
“…1h). As seen in the two figures, we see that pristine graphene is semiconductor, in good agreement with the previous report [15]. With lithium adsorption, the Fermi level of pristine graphene shifts to the conduction band.…”
Section: Adsorbed On Defective Graphenesupporting
confidence: 80%
See 1 more Smart Citation
“…1h). As seen in the two figures, we see that pristine graphene is semiconductor, in good agreement with the previous report [15]. With lithium adsorption, the Fermi level of pristine graphene shifts to the conduction band.…”
Section: Adsorbed On Defective Graphenesupporting
confidence: 80%
“…Heterogeneous structure composed of ultrathin MoS2/nitrogen-doped graphene nanosheets also exhibits highly reversible lithium storage [14]. Alternatively, Wang et al found that doping boron on graphene can be an effective method to enhance the lithium storage capacity, in which every boron atom can absorb 6 Li ions [15]. Wu et al followed this line to investigate Li adsorption on nitrogen doped and boron doped graphenes [16], while Zhou et al study the Li adsorption on nitrogen doped and boron doped CNTs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Boron doping leads the dirac point below the Fermi energy acting as a hole doping [30]. This transforms it into an electron-deficient system, increasing the electrophilic nature [13,[31][32][33], which leads to stronger adsorption of Li ions. Experimental studies show that reactivity of monolayer graphene towards electrophilic reactions is more near the periphery [34].…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Chan et al 41 have calculated 12 different metal adatoms on graphene systematically. They find that for the I-III groups adatoms, the interaction between the adatoms and graphene are ionic bonds and the electronic properties of graphene change little.…”
Section: Introductionmentioning
confidence: 99%